The High-Mobility Group Box-1 Nuclear Factor Mediates Retinal Injury after Ischemia Reperfusion - Dvoriantchikova, Galina (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. High-mobility group protein B1 (Hmgb1) is released from necrotic cells and induces an inflammatory response. Although Hmgb1 has been implicated in ischemia/reperfusion (IR) injury of the brain, its role in IR injury of the retina remains unclear. Here, the authors provide evidence that Hmgb1 contributes to retinal damage after IR. METHODS. Retinal IR injury was induced by unilateral elevation of intraocular pressure and the level of Hmgb1 in vitreous humor was analyzed 24 hours after reperfusion. To test the functional significance of Hmgb1 release, ischemic or normal retinas were treated with the neutralizing anti-Hmgb1 antibody or recombinant Hmgb1 protein respectively. To elucidate in which cell type Hmgb1 exerts its effect, primary retinal ganglion cell (RGC) cultures and glia RGC cocultures were treated with Hmgb1. To clarify the downstream signaling pathways involved in Hmgb1-induced effects in the ischemic retina, receptor for advanced glycation end products (Rage)-deficient mice (RageKO) were used. RESULTS. Hmgb1 is accumulated in the vitreous humor 24 hours after IR. Inhibition of Hmgb1 activity with neutralizing antibody significantly decreased retinal damage after IR, whereas treatment of retinas or retinal cells with Hmgb1 induced a loss of RGCs. The analysis of RageKO versus wild-type mice showed significantly reduced expression of proinflammatory genes 24 hours after reperfusion and significantly increased survival of ganglion cell layer neurons 7 days after IR injury. CONCLUSIONS. These results suggest that an increased level of Hmgb1 and signaling via the Rage contribute to neurotoxicity after retinal IR injury.